Camel Milk and Oxidative stress: Therapeutic potential against metabolic syndrome diseases - Musa, Khalid Hamid; Hamad, Essam M.; Elnour, Ahmed Adam Hassan Mohammed (Elsevier B.V., 2025)
Background: Camel milk (CM) has emerged as a potential therapeutic agent against oxidative stress (OS)-related disorders, particularly metabolic syndrome. CM contains bioactive compounds such as lactoferrin, α-lactalbumin, and Vitamin C, which contribute to its antioxidant properties. Objective: This review examines the antioxidant properties of camel’s milk and its bioactive components in combating OS and managing metabolic syndrome. Methods: A comprehensive literature review was conducted focusing on studies that explored the antioxidant properties of CM and its impact on OS and metabolic syndrome. Results: The findings indicated that CM possesses significant antioxidant properties, mainly attributed to its bioactive compounds, which can inhibit the production of various reactive oxygen species (ROS), thereby reducing OS. Evidence suggests that CM enhances the body's antioxidative defense, improves insulin sensitivity, and supports liver and kidney function. The multifaceted approach to CM offers a promising therapeutic strategy for OS-related disorders, notably those within the spectrum of metabolic syndromes. Conclusion: Considering its robust antioxidant qualities and capacity to regulate immune responses while enhancing metabolic health indicators, CM may be a valuable asset in the natural therapeutic repertoire to counter metabolic syndromes. Further clinical trials and research are essential to fully comprehend the therapeutic potential of CM, including dosage, long-term implications, and appropriate integration within extensive treatment schemes for metabolic syndromes and associated disorders. Recommendation: The use of CM to reduce OS requires further clinical studies to confirm its benefits and identify key compounds. Standardization of production and processing is essential for quality and safety, and research into potential risks and side effects is needed, especially for those with specific health conditions. Enhancing the accessibility, affordability, and sustainability of production methods is critical. Additionally, fortifying camel’s milk with vitamins and minerals can improve its nutritional value.